Studies on inhibition of xanthine oxidase activity of extracts from some medicinal mushrooms - Anh Tung, Vu; Thu, Huynh; Trong Hieu, Nguyen; Ngoc Hong Cam, Dang; Minh Hiep, Dinh (VNU Journal of Science: Natural Sciences and Technology, 2017)
Hyperuricemia is the well-known primary factor for developing gout, and closely related to all the metabolic disease such as obesity, hypertension, diabetes and cardiovascular. Xanthine oxidase is the enzyme of purine catabolism pathway in human, catalyzing the oxidation of xanthine to uric acid. Then, the accumulated uric acid causes hyperuricacidemia. Inhibition of xanthine oxidase is the potent therapeutic method for the treatment of hyperuricemia. On this study, we conducted the survey on the inhibition activity of xanthine oxidase of some extracts from the Lentinula sp., Tylopilus sp., Ophiocordyceps sinensis , Cordyceps pseudomilitaris and Cordyceps neovolkiana . The results showed that the ethanol, petroleum ether and ethyl acetate extracts of O. sinensis , the petroleum ether extract of Lentinula sp. exhibited inhibition activity of xanthine oxidase. Among them, the petroleum ether extract of O. sinensis showed the most effective on inhibition activity of xanthine oxidase at 250 µg/ml (26,21 ± 0,52 %).